Research progress on astrocyte autophagy in ischemic stroke - Su, Pei-Wei; Zhai, Zhe; Wang, Tong; Zhang, Ya-Nan; Wang, Yuan; Ma, Ke; Han, Bing-Bing; Wu, Zhi-Chun; Yu, Hua-Yun; Zhao, Hai-Jun; Wang, Shi-Jun (Frontiers in Neurology, 2022)
Ischemic stroke is a highly disabling and potentially fatal disease. After ischemic stroke, autophagy plays a key regulatory role as an intracellular catabolic pathway for misfolded proteins and damaged organelles. Mounting evidence indicates that astrocytes are strongly linked to the occurrence and development of cerebral ischemia. In recent years, great progress has been made in the investigation of astrocyte autophagy during ischemic stroke. This article summarizes the roles and potential mechanisms of astrocyte autophagy in ischemic stroke, briefly expounds on the crosstalk of astrocyte autophagy with pathological mechanisms and its potential protective effect on neurons, and reviews astrocytic autophagy-targeted therapeutic methods for cerebral ischemia. The broader aim of the report is to provide new perspectives and strategies for the treatment of cerebral ischemia and a reference for future research on cerebral ischemia.